Faktor Maternal Terhadap Kejadian BBLR - Rom lah; Theresia Anita; Anjelina Puspita Sari (Citra Delima Scientific journal of Citra Internasional Institute, 2021)
Background: Low Birth Weight Infants (LBW) is one of the causes of infant mortality which causes various health problems. Palembang City Health Office in 2017 stated that 29 cases of infant mortality, one of which was LBW. This study aimed to determine the relationship between maternal factors with the incidence of LBW. Methods: This study was an obsevastional with a cross sectional design. This study was conducted from May-September 2019, with a samples was 52 respondents. Samples were collected by observing retrospective data from the respondent's medical records. Data analysis technique was the Chi-Square. Results: The results showed a significant relationship between age and LBW (pv = 0.012), the parity with LBW were significantly related (pv=0.047), and there was no significant relationship the previous LBW history with LBW (pv =0.094). Conclusion: LBW raises various health problems in newborns. Therefore, it requires tighter supervision of pregnant women, especially pregnant women who are included in the risk factors.